Performance and Emission of Diesel Engine Fuelled with Water-in-Diesel Emulsion - Watanabe, Shunsuke; Ithnin, Ahmad Muhsin; Abdul Kadir, Hasannuddin; Abu Bakar, Muhd Aiman; Yahya, Wira Jazair (Journal of Advanced Vehicle System, 2017)
Power generation using combustion engine cause severe air polution. Research for a high efficient engine with less harmful emission is highly demanded. Water-in-Diesel (W/D) emulsion has a potential to reduce fuel consumption and harmful exhaust emission, especially nitrogen oxides (NOX) and particulate matter (PM). Experimental study was conducted by operating single cylinder MR MARK MC-D6500E diesel generator at different loading conditions while using two types of W/D emulsion containing different water contents (10 and 20 vol.%) with 1 vol.% of surfactant (span 80) as additive to stabilize the fuel. The effect of water on fuel consumption, exhaust temperature and emission has been studied and the results have been compared to conventional diesel fuel. The result showed NOx and PM were reduced up to 51% and 14% respectively by using W/D emulsion. Fuel consumption also was up to 10% improved by using W/D emulsion.